Analisis Peta Sebaran Spasial Pemadan Kebakaran (DAMKAR) Kota Jakarta Pusat: Indonesia - Vieri, Christian; Adamiri, Syahid Ali; Hirzi, Taris Zharfa (Jurnal Sains Geografi, 2023)
The fire station is a public facility that serves the community by providing first aid for incidents or disasters, especially fires. This facility also has another function as a firefighter's workplace. Analysis of the distribution of fire stations in Central Jakarta City uses the shape file of Central Jakarta City administration, and OpenStreetMap and Google Earth to find the location of fire stations in Central Jakarta City. The analytical methods applied in this project include quantitative description analysis and the Nearest neighbor analysis method, with the results of data processing attached to a map to analyze the spatial distribution pattern of fire stations in Central Jakarta City. The results of the analysis show that the pattern of distribution of firefighter posts in Central Jakarta City is spread across 7 sub-districts, and the resulting distribution pattern is that firefighter posts in Central Jakarta City are spread randomly. This study provides information about the distribution of fire extinguishers and determines the pattern of fire stations in Central Jakarta.